Cost of lost productivity from acute respiratory infections in South America - Gabriela B.G. Mosegui; Fernando Antoñanzas; Cid M. de Mello Vianna (Pan American Health Organization, 2023)
Objectives. To estimate the burden of permanent productivity losses caused by acute respiratory infections in South American countries in 2019. Methods. Mortality data from the Global Burden of Disease Study 2019 were analyzed to estimate the burden of disease attributable to acute respiratory infections. An approach based on the human capital method was used to estimate the cost of permanent productivity losses associated with respiratory diseases. To calculate this cost, the sum of the years of productive life lost for each death was multiplied by the proportion in the workforce and the employment rate, and then by the annual minimum wage or purchasing power parity in United States dollars (US$) for each country in the economically active age groups. Separate calculations were done for men and women. Results. The total number of deaths from acute respiratory infections in 2019 was 30 684 and the years of productive life lost were 465 211 years. The total cost of permanent productivity loss was about US$ 835 million based on annual minimum wage and US$ 2 billion in purchasing power parity, representing 0.024% of the region's gross domestic product. The cost per death was US$ 33 226. The cost of productivity losses differed substantially between countries and by sex. Conclusion. Acute respiratory infections impose a significant economic burden on South America in terms of health and productivity. Characterization of the economic costs of these infections can support governments in the allocation of resources to develop policies and interventions to reduce the burden of acute respiratory infections.